2006
DOI: 10.1002/pbc.21016
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma in a 9‐year‐old girl with ataxia‐telangiectasia

Abstract: A 9-year-old female with ataxia-telangiectasia (AT) presenting with papillary thyroid carcinoma and lymph nodes involvement is reported. We discuss this novel association, the general risk of neoplasic complications in these patients, the natural history of thyroid carcinoma in the pediatric population and the potential link between thyroid carcinogenesis and ataxia-telangiectasia mutated gene (ATM) mutation. We also expose our therapeutic attitude, according to both clinical status and particular genetic back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There is only one other A-T child reported by Brasseur et al 3 ; that was a 9-yearold girl with papillary carcinoma. Suarez et al 13 identified 279 patients with A-T and revealed 69 patients with cancer.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is only one other A-T child reported by Brasseur et al 3 ; that was a 9-yearold girl with papillary carcinoma. Suarez et al 13 identified 279 patients with A-T and revealed 69 patients with cancer.…”
Section: Discussionmentioning
confidence: 92%
“…Other features include retardation of somatic growth, premature aging, radiosensitivity and predisposition to cancer 2 . Definitive diagnosis is made by revealing a disease causing mutation on ATM gene which was identified in 1995 in 11q22-23, coding for a protein implicated in genomic homeostasis in case of radio-induced DNA double-strand breaks [1][2][3] .…”
mentioning
confidence: 99%
“…Patients with A-T have an increased incidence of neoplasms, especially lymphoma and leukaemia, but also breast, liver, gastric, and oesophageal malignancies [ 79 ]. Patients with A-T and thyroid cancer have been reported [ 80 ]. Cells from patients with A-T have an increased sensitivity to ionizing radiation, so standard radiotherapy/radiomimetic drugs to treat cancer should be avoided/used with caution.…”
Section: Cancer Predisposition Syndromes With Thyroid Cancermentioning
confidence: 99%
“…The high risk of cancer and radiosensitivity are known in AT patients but few data about the incidence of TC are available. Six cases of TC in patients affected by ATM were described [16][17][18][19][20] and three of them were diagnosed at autopsy (Table 1B). Surgery is the gold standard for managing thyroid cancer and total thyroidectomy is often recommended for PTC, which tends to occur bilaterally and multifocally.…”
Section: E T T E R T O T H E E D I T O R Thyroid Carcinoma In Two Pat...mentioning
confidence: 99%